Uncanny experiences as therapeutic events - Kia Andell; Harley Bergroth; Marja-Liisa Honkasalo (Routledge, 2022)
Encounters with the ‘uncanny’ – or ‘supernatural’ as it is often labelled in Euro-American societies – are commonly conceived of as a ‘premodern’ (Latour, 1993) mode of experience and characteristic of cultural ‘otherness’ (Kapferer, 2002). However, social scientific research has shown that such experiences are also commonly reported in post-industrial, contemporary social settings (see Dein, 2012). It seems that disenchantment, as Weber (1922/1967: 139) put it, has only had a limited effect, as people’s engagements with the supernatural, the magical, and the otherworldly have not vanished in technoscientific societies with highly specialised education systems (see Josephson-Storm, 2017). By uncanny experiences we refer to ‘extraordinary’ sensory and embodied experiences that are often unexpected, uncontrollable and quite powerful. 1 Such experiences range from premonitions and visions to encounters with spiritual or otherworldly beings, and from telepathic communication to contacts with the deceased.
Assembling Therapeutics: Cultures, Politics and Materiality